Does quality matter? Examining the influence of product quality and source on Japanese beef imports - Christina G. Slater; Andrew Muhammad; Karen L. DeLong (Journal of Agriculture and Food Research)
Product quality is essential, as it influences consumer preferences and, hence, affects imports. In this study, we employed a demand system framework to estimate source-differentiated beef demand in Japan. Additionally, we evaluated whether the quality attributes of chilled versus frozen beef were significant in explaining trade flows. Using quarterly trade data, we estimated Japanese beef demand by exporting source (e.g., Australia, U.S.) and product quality (chilled and frozen). We used different models based on assumptions about quality (unrestricted, quality aggregated, and quality separability) and compared the demand estimates and resulting elasticities across models. The importance of quality was also verified by separability and aggregation likelihood-ratio tests.Results indicate that quality matters. In fact, likelihood-ratio tests indicate that preferences for chilled and frozen beef may even be independent. That is, the demand for chilled beef imports could be estimated separately from frozen beef imports. However, resulting elasticity estimates did not significantly differ when quality attributes were considered, except for U.S. chilled beef where the own-price elasticity was statistically different between the unrestricted model (−0.4) and quality-aggregated model (−1.2). However, we found no significant difference between the elasticities from the quality-separability and quality-aggregated models regardless of source. Results provide insights into Japanese beef import demand, which is important considering Japan is the third largest beef importer in the world.